Tobacco taxation: the importance of earmarking the revenue to health care and tobacco control - Vardavas, Constantine I (BioMed Central, 2012)
BACKGROUND: Increases in tobacco taxation are acknowledged to be one of the most effective tobacco control interventions. This study aimed at determining the mediating role of socioeconomical status (SES) and the earmarking of revenue to healthcare and tobacco control, in influencing population support for the adoption of a 2 Euro tobacco tax increase in Greece, amid the challenging economic environment and current austerity measures. METHODS: Data was collected from two national household surveys, the “Hellas Health III” survey, conducted in October 2010 and the "Hellas Tobacco survey” conducted in September 2012. Data was analyzed from 694 and 1066 respondents aged 18 years or more, respectively. Logistic regression models were fitted to measure the adjusted relationship between socio-economic factors for the former, and support for increased taxation on tobacco products for the latter. RESULTS: In 2012 amidst the Greek financial crisis, population support for a flat two euro tax increase reached 72.1%, if earmarked for health care and tobacco control, a percentage high both among non-smokers (76%) and smokers (64%) alike. On the contrary, when not earmarked, only 43.6% of the population was in support of the equivalent increase. Women were more likely to change their mind and support a flat two-euro increase if the revenue was earmarked for health care and tobacco control (aOR = 1.70; 95% C.I: 1.22-2.38, p = 0.002). Furthermore, support for an increase in tobacco taxation was not associated with SES and income. CONCLUSION: Despite dire austerity measures in Greece, support for an increase in tobacco taxation was high among both smokers and non-smokers, however, only when specifically earmarked towards health care and tobacco control. This should be taken into account not only in Greece, but within all countries facing social and economic reform.